Control of Antenna Azimuth Position using Fractional order Lead Compensator - Govinda Kumar, E; Prakash, R; Rishivanth, S; A. Anburaja, S; Gopi Krishna, A (International Journal of Engineering and Technology, 2018)
This paper addresses the position control of antenna azimuth using proportional and integral (PI) controller and lead compensators. The fractional order calculus plays an important role for designing the robust control. The fractional order lead compensator is proposed for enhancing the closed loop performance of azimuth position control of antenna system. From the comparison of the closed loop responses, the proposed lead compensator delivers a superior closed loop performance when compared with PI controller and lead compensator.Â